Analisa Penerimaan Sistem Pembelajaran E-Learning Pada Masa Pandemic Menggunakan Structural Equation Model-Partial Least Square - Ensiwi Munarsih; Agnes Rendowaty; Rini Yunita (UNIVERSITAS INDO GLOBAL MANDIRI)
The Covid 19 pandemic has had a major influence on the order of human life at this time, including in the world of education. Teachers and educators as essential elements in teaching are required to undertake an unprecedented large-scale migration from traditional face-to-face education to online education or distance education. One of the learning systems used is the e-learning learning system. E-learning is a learning system that is carried out using electronic media. This research was conducted to test user acceptance of the e-learning learning system using the Technology Acceptance Model (TAM). TAM is an analytical model to determine user behavior regarding the acceptance of a technology Testing is done by measuring the influence between variables in the TAM model which includes the variables Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavioral Intention, and Actual Usage. Testing the influence of factors is carried out using the Structural Equation Model (SEM) - Partial Least Squares (PLS). Evaluation data is obtained from questionnaires distributed to users of the e-learning system. The results show that there is a direct influence between perceived usefulness and perceived ease of use on user behavioral attitudes which have implications for behavioral intentions to use technology (e-learning). This means that users of the e-learning system have the perception that the e-learning system is easy to use so that users can accept the e-learning system and continue to use it in their daily lives Keywords : e-learning, Technology Acceptance Model, Structural Equation Model, Partial Least Squares